Development of Deletion Lines for Chromosome 3D of Bread Wheat - Svačina, Radim; Karafiátová, Miroslava; Malurová, Magdaléna; Serra, Heïdi; Vítek, Dominik; Endo, Takashi R.; Sourdille, Pierre; Bartoš, Jan (Frontiers in Plant Science, 2020)
The identification of genes of agronomic interest in bread wheat (Triticum aestivum L.) is hampered by its allopolyploid nature (2n = 6x = 42; AABBDD) and its very large genome, which is largely covered by transposable elements. However, owing to this complex structure, aneuploid stocks can be developed in which fragments or entire chromosomes are missing, sometimes resulting in visible phenotypes that help in the cloning of affected genes. In this study, the 2C gametocidal chromosome from Aegilops cylindrica was used to develop a set of 113 deletion lines for chromosome 3D in the reference cultivar Chinese Spring. Eighty-four markers were used to show that the deletions evenly covered chromosome 3D and ranged from 6.5 to 357 Mb. Cytogenetic analyses confirmed that the physical size of the deletions correlated well with the known molecular size deduced from the reference sequence. This new genetic stock will be useful for positional cloning of genes on chromosome 3D, especially for Ph2 affecting homoeologous pairing in bread wheat.